Measurement of Educational Inequality in Nepal - Thapa, Surya Bahadur (Economic Journal of Nepal, 2015)
Education is considered as an important instrument of overall development. Its distribution is directly linked with the welfare of the people. An unequal distribution represents large welfare loss. In this context, this article measures educational inequality in terms of average years of schooling and Gini Coefficient of education based on the secondary data provided by the Central Bureau of Statistics. The research found that the average years of schooling is in increasing trend and the Gini Coefficient of education is in decreasing trend over the years. The study also found that the average years of schooling and Gini Coefficient of education are inversely related. Economic Journal of Nepal Vol. 34, No. 2, Issue no. 134, 2011